Effect of topography and soil on the distribution of under canopy trees of Garcinia (Guttiferae) in lowland forest of Peninsular Malaysia - Saleh, M. Nazre; Latiff, A.; Mohamad Kasim, Mohamad Roslan (2009)
The distribution and aggregation of species in tropical forests is known to have certain preferences based on the edaphic factors such as topography types and soil series and this study was carried out to see the distribution of 16 Garcinia species in lowland dipterocarp forest in Pasoh Forest Reserve with those edaphic factors. Even though there have been many studies in large scale areas with a larger group of species to see the relationship of edaphic factors with species distribution, very few studies have been carried out on individual species especially for under-canopy or lesser known species. Garcinia is an under-canopy tree species in tropical South East Asian forests with no commercial values but mostly known because of their edible fruits. Based on published topography and soil series maps in 50 ha plot, the preferences of Garcinia trees were analysed and calculated. Results showed that Garcinia trees could be found on all types of topography and soil but most trees are distributed very well on the flatland and well-drained alluvium soils rather than other areas. The least number of stems found are in the top (highest) topography and poorly-drained (prone to flood) alluvium soil. However, at species level, there are significant preferences of each Garcinia species on the different type of topography and soil. This shows that different type of topography and soil play significant effect on the distribution of Garcinia trees in tropical lowland forest.